PLACE EVENT MARKETING IN THE ASIA PACIFIC REGION branding and promotion in. - Cudny, Waldemar ([S.l.] : ROUTLEDGE, 2021)
This book explores the fascinating phenomenon of place event marketing in the Asia Pacific region. It examines procedures in the promotion and branding of places that use events to shape their identities. It considers how events are used in forming a branded image of a place and disseminate information about it. This innovative book offers theoretical insights of the opportunities and challenges related to place event marketing. With contributions from leading thinkers in the field, chapters also draw on empirical examples to showcase a variety of events across the Asia Pacific, such as MICE, sporting events, festivals, and religious and cultural celebrations. The book explores the importance of such events for the socio-economic development of urban regions. Today, the Asia Pacific is one of the world's fastest developing regions and its rising economic power is accompanied by the growing importance of the tourism and event sector. The book is a unique study relating to a very exceptional region of the world. The role of events in tourism development and the rise of the region's soft power is presented through carefully selected examples of cities from different countries. The book concludes with commentary on the future directions for research in this area. Written in an accessible style, this book will be of great interest to students, scholars, and practitioners working in events studies, urban studies, tourism, place branding and promotion, business and management studies, geography, sociology, and sport and leisure studies.
OCLC-licensed vendor bibliographic record.
Keywords: Place marketing -- Pacific Area; Special events -- Marketing; Economic development -- Pacific Area; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism